Serum Vitamin B12 Level in Children with Type 1 Diabetes - Pradhan, Santosh; Thapa, Subhana; Shrestha, Pradeep Krishna; Jha, Bharat (Journal of Nepal Health Research Council, 2025)
Background: Type 1 Diabetes Mellitus is known to be associated with multiple co-morbidities. Vitamin B12 deficiency is a potential co- morbidity that might have been overlooked in these patients. The aim of this study is to evaluate the serum level of vitamin B 12 in a well-defined population of Type 1 diabetes.Methods: The cross sectional study carried out on 40 patients with Type 1 Diabetes Mellitus visiting endocrinology unit in Kanti children’s Hospital, Kathmandu, Nepal. Thirty healthy non diabetics were also selected. Serum C-peptide, vitamin B12, creatinine, blood glucose level and glycosylated hemoglobin were assessed in both groups. SPSS ver. 22 was used to analyze the data.Results:The mean serum vitamin B12 level of the diabetic group was 206.92±82.18 pmol/L. Among the population 40.0% i.e. 16 out of 40 were found to be deficient and 37.5 % i.e. 15 out of 40 were subclinically deficient. Whereas the mean serum vitamin B12 level of the non diabetic group was 340.71±136.02pmol/L. Out of 30 only 2(6.7%) were deficient, 8 (26.75%) were found to be subclinically deficient. Significant difference was noticed in the mean serum level of vitaminB12 between these two groups.Conclusions: This study shows the presence of low serum vitamin B12 levels in Type 1 Diabetics. The routine screening for this condition along with confirmatory test and detail clinical examination could benefit the patients with Type 1 diabetes.Keywords: Autoimmune disease; Type 1 Diabetes mellitus; Vitamin B12.